ANALISIS MEMBANGUN ORIENTASI PASAR USAHA KECIL DAN MENENGAH (UKM) MELALUI COMPETITIVE ADVANTAGE DALAM MENCAPAI KINERJA PEMASARAN (STUDI PADA UKM SENTRA BATIK SEMARANGAN DI KOTA SEMARANG) - Irmadiani, Nadia Dwi (Universitas Pakuan, 2016)
ABSTRACTMarket orientation as a business philosophy can be defined by how an organization implements the concept of market orientation in its activities and behavior. Market orientation is one of the factors that influence competitive advantage. The competitive advantage could demonstrate the companys ability to achieve economic benefits in connection with the profits that can be achieved by competitors in the market within the same industry. While marketing performance is influenced by the environment of the company. Thus the success of a company can be seen from how it responses to the pressure from its environment in facing the competitive market. This research is aimed to analyse the market orientation of small, and medium scale business of superior product of batik Semarangan in Semarang through competitive advantage in achieving its marketing performance. The research is done in small, and medium scale business that create Semarangan batik in Semarang. It takes 40 small, and medium scale of business. The data is obtained by using questionnaire instrument while the variables influence is tested by using the path analysis. The result shows that market orientation has a positive influence to the competitive advantage and marketing performance. Meanwhile the competitive advantage has a positive influence to marketing performance. The research also finds the proof that competitive advantage is able to mediate the market orientation and marketing performance.Â Keywords: Market Orientation, Competitive Advantage, and Marketing Performance